Zooplankton as a food resource of juvenile fish in the littoral shallows of the Ry-binsk reservoir - V. N. Stolbunova; I. A. Stolbunov (Vìsnik Dnìpropetrovsʹkogo Unìversitetu: Serìâ Bìologìâ, Ekologìâ, 2010)
Species composition, dominant species and quantitative characteristics of zooplankton in different habitats of the littoral shallow part of the Rybinsk Reservoir were studied at the end of august 2009. In the structure of zooplankton community 75 taxa have been found among which crustaceans are prevailed. The most of them belong to littoral forms. The highest values of abundance and biomass of zooplankton and density accumulation of young fish are recorded in mouth parts of rivers inflowing the reservoir.